Case study report on efficacy of vitamin D in physiotherapy - DR. S.S. SUBRAMANIAN, Ph.D,,; MS. S. SUGANTHI,; MR. N. MOHAMMED SHABEER, (International Journal of Pharma and Bio Sciences, 2017)
It is well known that minerals and vitamins are most important for musculoskeletal function. Our objective was to analyse the efficacy of Vitamin D in physiotherapy and to evaluate clinical implications of Vitamin D with pain and exercises. 40 year male with pain and stiffness in cervical region was treated with exercises, with an increased fatigue, repeated stiffness, recurrence of pain, we have referred the subject for Vitamin D evaluation and treatment to physician. As Vitamin D was only 10 ng /ml, the subject with due medicine, followed by exercises has shown clinical improvement. Thus clinical manifestations of physical sign are of most importance with physiotherapy is evident.